We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
113
1
avatar+1206 

 How did \(-3i\bar{z}\) become -3b-3ia?  When I expanded it, I got \(-3i(a-bi)=-3ia-3bi\)?

 Apr 14, 2019
 #1
avatar+102948 
+1

-3i (z conjugate)  =

 

-3 i ( a - bi)  =

 

-3i a   + 3b i^2  =

 

-3b - 3 i a

 

 

cool cool cool

 Apr 14, 2019

4 Online Users